Functional and patient-reported outcome versus in-hospital costs after traumatic acute subdural hematoma (t-ASDH): a neurosurgical paradox? - van Dijck, Jeroen T. J. M. (Acta Neurochir (Wien), 2019)
BACKGROUND: The decision whether to operate or not in patients with a traumatic acute subdural hematoma (t-ASDH) can, in many cases, be a neurosurgical dilemma. There is a general conception that operating on severe cases leads to the survival of severely disabled patients and is associated with relatively high medical costs. There is however little information on the quality of life of patients after operation for t-ASDH, let alone on the cost-effectiveness. METHODS: This study retrospectively investigated patient outcome and in-hospital costs for 108 consecutive patients with a t-ASDH. Patient outcome was assessed using the Glasgow Outcome Score (GOS) and the Traumatic Brain Injury (TBI)–specific QOLIBRI questionnaire. The in-hospital costs were calculated using the Dutch guidelines for costs calculation. RESULTS: Out of 108 patients, 40 were classified as having sustained a mild (Glasgow Coma Scale (GCS) 13–15), 19 a moderate (GCS 9–12), and 49 a severe (GCS 3–8) TBI. As expected, mortality rates increased with higher TBI severity (23%, 47%, and 61% respectively), whereas the chance for favorable outcome (GOS 4–5) decreased (72%, 47%, and 29%). Interestingly, the mean QOLIBRI scores for survivors were quite similar between the TBI severity groups (61, 61, and 64). Healthcare consumption and in-hospital costs increased with TBI severity. In-hospital costs were relatively high (€24,980), especially after emergency surgery (€28,670) and when additional ICP monitoring was used (€36,580). CONCLUSIONS: Although this study confirms that outcome is often “unfavorable” after t-ASDH, it also shows that “favorable” outcome can be achieved, even in the most severely injured patients. In-hospital treatment costs were substantial and mainly related to TBI severity, with admission and surgery as main cost drivers. These results serve as a basis for necessary future research focusing on the value-based cost-effectiveness of surgical treatment of patients with a t-ASDH. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s00701-019-03878-5) contains supplementary material, which is available to authorized users.